2008
DOI: 10.5194/hessd-5-1511-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scale effects on runoff generation in meso-scale and large-scale sub-basins in the Luanhe River Basin

Abstract: Abstract. The scale effects on runoff coefficients have been observed by several researchers on plots or small watersheds, however, little research has been done on meso-scale and large-scale catchments. So six meso-scale and large-scale sub-basins of the Luanhe river basin, in northeast of China, were selected for calculating the runoff coefficients of single event during 1956–2002. An obvious reduction in average runoff coefficients from 0.43 (Liuhe basin) to 0.10 (Luanhe basin) was found with increasing bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…The same appeared to occur at subcatchment level, where sediment fluxes were even lower. Several studies have also shown lower unit-area runoff and sediment fluxes on stream channels than hillslopes (Constantz, 1998;Feng and Li, 2008;Goransson et al, 2013;Xu, 2014) due to lower slope gradients which promote high infiltration and sediment deposition (Doble et al, 2012;Eder et al, 2014). Results of cumulative runoff (Table 2) showed great annual runoff microcatchment level, which in some years (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…The same appeared to occur at subcatchment level, where sediment fluxes were even lower. Several studies have also shown lower unit-area runoff and sediment fluxes on stream channels than hillslopes (Constantz, 1998;Feng and Li, 2008;Goransson et al, 2013;Xu, 2014) due to lower slope gradients which promote high infiltration and sediment deposition (Doble et al, 2012;Eder et al, 2014). Results of cumulative runoff (Table 2) showed great annual runoff microcatchment level, which in some years (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…The erosion variables in this paper are annual data, based on natural precipitation, corresponding to hydrological years (Table ). The age of trials, time periods for which experiments had been running, varied from 1 to 45 years [e.g., Feng and Li , ], with 63% of the studies being 1 year old. In cases where erosion variables were reported for more than 1 year, each year's data were treated as a separate and independent measurement for purposes of this meta‐analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Dicha variable se determinó históricamente en función de la precipitación acumulada de los cinco días previos, P 5, la que condiciona el valor que toma CN medio de una cuenca para condiciones antecedentes secas (P5 < 23 mm) o húmedas (P5 > 40 mm) (SCS, 1972). Sin embargo, el NRCS (2004a) advierte que no existe correlación entre P5 y la variabilidad del CN y, en consecuencia, el uso de tablas de P5 ya no es compatible ni aprobado por NRCS (Grabau et al, 2009). Sobre la base de los resultados de Hjelmfelt et al (1982), se postula que el CN constituye una variable aleatoria con tendencia central de tipo II y límites de error I y III, correspondientes al 90 y 10 % de probabilidad de excedencia, respectivamente (Grabau et al, 2009).…”
Section: Introductionunclassified